Does Minimally Invasive Percutaneous Posterior Instrumentation Reduce Risk of Proximal Junctional Kyphosis in Adult Spinal Deformity Surgery? A Propensity-Matched Cohort Analysis. Issue 1 (January 2016) - Mummaneni, Praveen V.; Park, Paul; Fu, Kai-Ming; Wang, Michael Y.; Nguyen, Stacie; Lafage, Virginie; Uribe, Juan S.; Ziewacz, John; Terran, Jamie; Okonkwo, David O.; Anand, Neel; Fessler, Richard; et al.
Abstract : BACKGROUND: Proximal junctional kyphosis (PJK) is a known complication after spinal deformity surgery. One potential cause is disruption of posterior muscular tension band during pedicle screw placement. OBJECTIVE: To investigate the effect of minimally invasive surgery (MIS) on PJK. METHODS: A multicenter database of patients who underwent deformity surgery was propensity matched for pelvic incidence (PI) to lumbar lordosis (LL) mismatch and change in LL. Radiographic PJK was defined as proximal junctional angle >10°. Sixty-eight patients made up the circumferential MIS (cMIS) group, and 68 were in the hybrid (HYB) surgery group (open screw placement). RESULTS: Preoperatively, there was no difference in age, body mass index, PI-LL mismatch, or sagittal vertical axis. The mean number of levels treated posteriorly was 4.7 for cMIS and 8.2 for HYB ( P < .001). Both had improved LL and PI-LL mismatch postoperatively. Sagittal vertical axis remained physiological for the cMIS and HYB groups. Oswestry Disability Index scores were significantly improved in both groups. Radiographic PJK developed in 31.3% of the cMIS and 52.9% of the HYB group ( P = .01). Reoperation for PJK was 4.5% for the cMIS and 10.3% for the HYB group ( P = .20). Subgroup analysis for patients undergoing similar levels of posterior instrumentation in the cMIS and HYB groups found a PJK rate of 48.1% and 53.8% ( P = .68) and a reoperation rate of 11.1% and 19.2%, respectively ( P = .41). Mean follow-up was 32.8 months. CONCLUSION: Overall rates of radiographic PJK and reoperation for PJK were not significantly decreased with MIS pedicle screw placement. However, a larger comparative study is needed to confirm that MIS pedicle screw placement does not affect PJK. ABBREVIATIONS: cMIS, circumferential minimally invasive surgery HYB, hybrid LL, lumbar lordosis MIS, minimally invasive surgery PI, pelvic incidence PJK, proximal junctional kyphosis PPI, percutaneous posterior instrumentation SVA, sagittal vertical axis UIV, uppermost instrumented vertebra VAS, Visual Analog Scale